EVALUATING THE EFFECTIVENESS OF MOBILE APPLICATIONS IN ENHANCING LEARNING AND DEVELOPMENT - Rocque, Sarvesh Raj (International Journal of Innovative Technologies in Social Science, 2022)
This paper aims to examine how mobile applications relate to learning and development. It will determine whether these two factors are properly intertwined and whether these two factors are fully justified in being related. As a result of examining the literature, and reviewing the results of our survey, we have developed a framework for research. This framework will provide evidence that mobile technologies have a positive impact on classroom performance both directly and indirectly. These technologies foster the learning and development process at all levels, which ultimately enhances the individual’s competency by equipping him or her with a more comprehensive skill set. A total of one hundred and eighty interviews were conducted with educators during the research process. These interviews were conducted to develop the findings presented in this article on the impact of mobile applications in the classroom as a result of the research process. There is a growing body of research that suggests the use of mobile apps can be an effective tool for fostering creativity, learning, and development in a variety of settings, both formal and informal. They have been shown to be beneficial in a number of ways when it comes to promoting learning and development. When compared to traditional methods of teaching, mobile apps have shown to be more effective in promoting holistic learning and increasing learning speed than traditional methods of teaching, especially when it comes to promoting holistic learning and increasing learning speed. With the introduction of mobile applications to the education sector, many novel learning strategies have been developed within this sector as a result of the introduction of mobile apps. The use of mobile devices in the classroom has resulted in a number of changes in this respect. The use of mobile apps can provide students with a variety of games that are designed to encourage them to engage in a positive thought process as well as allow them to gain a deeper understanding of what they are learning as they interact with the games and become engaged with them on a more personal level. "Mobile learning" refers to the use of mobile devices and apps in order to facilitate the learning process in an attempt to facilitate the learning process mobile devices and apps in order to facilitate the learning process. The term may also refer to the way in which mobile technology can be used to support a continuous learning environment.